The development of a writing system for Aymara - Llanque Chana, Domingo (1987)
Before opting for one or another form of writing for a traditional language, it is necessary to ask yourself who is going to write and for what. If a certain writing system is sought for an unlettered language, it is not to satisfy the curiosity of the linguist but to facilitate written communication between its potential users and to record in writing, and thus perpetuate, the knowledge, traditions and feelings with which the The people who use this language contribute to our better understanding of the universe and of things, in the search for a better world for all human beings. That is, we are not looking to write a traditional language just for academic interest or because we are trying to codify it before it is too late and its speakers stop using it, and thus, at least, have some written samples of the language saved. e jealous archives so that, like museum pieces, they can be consulted by scholars.